2010
DOI: 10.3109/09637480903517788
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and chemical difference in fruit of differentActinidiasp.

Abstract: The present research aimed at evaluating the vitamin C, total phenolic content (TPC), phenolic compounds, carotenoids, and chlorophyll contents, as well as antioxidant activity (AAC) of six Actinidia species fruit. Vitamin C, phenolic compounds, carotenoids and chlorophylls were measured using high-performance liquid chromatography. TPC was determined using the Folin-Ciocalteau reagent, and AAC using 2,2-diphenyl-1-picryl hydrazyl (DPPH) assay. The highest concentrations of vitamin C and TPC were found for Act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
95
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(104 citation statements)
references
References 26 publications
6
95
2
1
Order By: Relevance
“…One sample of A. arguta, AA-HSP-TD, had extremely high SSC (average of 30.8%). This value was much higher than that found by others: 14%-15% in an unknown cultivar (Huang et al, 2004), 10.5% in 'Mitsu-ko' (Okamoto and Goto, 2005), 11.1%-12.8% in wild collections from Japan (Kataoka et al, 2010), 16.6% in 'Ananasnaya' and 16.8% in 'Weiki' (Latocha et al, 2010), and 10.2%-17.0% in two cultivars and 14 local collections from Japan (Kim et al, 2012); kiwifruit 'Hayward' was 13.2%-14.6% (Tavarini et al, 2008). Our data probably represent one of the highest SSC levels reported to date in A. arguta and in the genus Actinidia.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…One sample of A. arguta, AA-HSP-TD, had extremely high SSC (average of 30.8%). This value was much higher than that found by others: 14%-15% in an unknown cultivar (Huang et al, 2004), 10.5% in 'Mitsu-ko' (Okamoto and Goto, 2005), 11.1%-12.8% in wild collections from Japan (Kataoka et al, 2010), 16.6% in 'Ananasnaya' and 16.8% in 'Weiki' (Latocha et al, 2010), and 10.2%-17.0% in two cultivars and 14 local collections from Japan (Kim et al, 2012); kiwifruit 'Hayward' was 13.2%-14.6% (Tavarini et al, 2008). Our data probably represent one of the highest SSC levels reported to date in A. arguta and in the genus Actinidia.…”
Section: Discussioncontrasting
confidence: 44%
“…Wide variation in AAC has also been observed among cultivars, with the following values reported on a mg/100 g FW basis: 'Lande', 700; 'Pavlovskaja', 600; and 'VIR-1', 850 (Chesoniene et al, 2004); 'Dr Szymanowski', 1008 (Latocha et al, 2010); and an unknown cultivar, 211 (Zuo et al, 2012). We found much larger variability in AAC in A. arguta, with a more than eight-fold difference between the lowest and highest values.…”
Section: Discussionmentioning
confidence: 99%
“…According to Latocha et al (2010), the content of total phenols in A. arguta was 79 mg/100 g FW. Wang (2013) reported that the content of TP in the fruits of A. arguta was 214.8 mg/100 g, whereas Zuo et al (2012) claimed that value to be higher.…”
Section: Discussionmentioning
confidence: 99%
“…참다래에는 페놀성 화합물 뿐만 아니라, 비타민 C, 미 네랄, 엽록소, 카로티노이드와 같은 건강에 유익한 다양한 생 리활성물질이 함유되어 있다 (Tavarini et al, 2008;Latocha et al, 2010). 참다래의 페놀성 화합물이 활성산소에서 야기 되는 산화적 스트레스에 의한 신경세포 손상을 보호했다 (Kim et al, 2010).…”
Section: Samplesunclassified